Adverse Birth Outcomes in Botswana Among Women With Vertically or Horizontally Acquired Human Immunodeficiency Virus. (15th June 2020) - Fennell, Christina; Seage, George R; Zash, Rebecca; Phiri, Kelesitse; Diseko, Modiegi; Mayondi, Gloria; Lockman, Shahin; Sekoto, Tumalano; Mmalane, Mompati; Makhema, Joseph; Shapiro, Roger
Abstract: Background: Women with vertically acquired HIV (VHIV) may have a greater risk of adverse birth outcomes than women with horizontally acquired HIV (HHIV). Methods: The Tsepamo study performed birth outcomes surveillance at 8 government delivery sites in Botswana from July 2014 through March 2019. Pregnant women diagnosed with HIV before their 11th birthday received VHIV status, and other women had HHIV. Small for gestational age (SGA), preterm delivery (PTD), stillbirth, and neonatal death were compared using χ2 and Fisher's exact tests. Log-binomial regression models determined risk ratios (RRs). Results: VHIV women (n = 402) aged 15–27 years were identified over 4 years of surveillance and compared with HHIV women (n = 8465) of the same age. VHIV women were more likely to use nevirapine (NVP)-based antiretroviral treatment (ART) in pregnancy and to have SGA and very SGA infants, but less likely to have very PTD infants. In unadjusted analyses, VHIV women had a higher risk of any adverse birth outcome combined (RR = 1.21, 95% confidence interval [CI], 1.08–1.36). After adjusting for potential confounders, particularly use of NVP-based regimens, the risk of adverse birth outcomes among VHIV and HHIV women was similar. Conclusions: NVP-based ART is a primary and modifiable risk factor for adverse birth outcomes. Updating ART regimens could improve birth outcomes for women with HIV. Abstract : Information regarding adverse birth outcomes among women with vertically acquired HIV is not well known in high HIV prevalence settings. NVP-based ART was noted as a primary risk factor.